Reward‐based, task‐setting education strategy on glycemic control and self‐management for low‐income outpatients with type 2 diabetes. Issue 4 (18th October 2013) - Guo, Honglei; Tian, Xiaoli; Li, Rixia; Lin, Jingna; Jin, Nana; Wu, Zhongming; Yu, Demin
Abstract Aims/Introduction The purpose of the study was to determine the feasibility and effect of a reward‐based, task‐setting strategy for low‐income outpatients with type 2 diabetes. Materials and Methods Indigent diabetes outpatients without glucometers were eligible to participate in this trial. A total of 132 cases were randomly recruited. Participants in group B used glucometers for self‐monitoring at no cost. Group A participants could keep the glucometers only if the glycosylated hemoglobin level declined compared with the baseline visit; for those not achieving a reduction in the glycosylated hemoglobin level, the glucometers would have to be returned. Group C served as the control group without self‐monitoring setout. Diabetes education was provided to all groups. Metabolic indices and self‐management were evaluated after 6 months of follow up. Results Group A had a significant decline in the glycosylated hemoglobin level (−0.97%) and medical costs (−159 yuan) compared with the baseline visit, whereas groups B and C had a decrease in the glycosylated hemoglobin levels alone (−0.62 and −0.57%, respectively). The body mass index did not change significantly in any group. There was a statistical difference in the glycosylated hemoglobin level of group A compared with groups B and C. Self‐management in group A improved the outcome relative to groups B and C. Conclusions This preliminary evidence suggests that the program is feasible, acceptable for improving patient self‐management, and cost‐effective in reducing the glycosylated hemoglobin level and medical costs.